2019
DOI: 10.3892/mco.2019.1829
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and positive surgical margins as prognosticators for upper urinary tract urothelial carcinoma patients undergoing radical nephroureterectomy

Abstract: Chronic kidney disease (CKD) is a common condition among elderly patients and has been reported to be a biomarker for the presence of malignant disease. In addition, unfavorable outcomes for patients with upper tract urothelial carcinoma (UTUC) undergoing radical nephroureterectomy can be due to independent clinical factors. Therefore, the present study analyzed the clinicopathological data of patients with UTUC, who underwent radical nephroureterectomy at our institution, to clarify whether preoperative CKD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The major characteristics of the 15 eligible studies are presented in Table 1. These studies were published from 2015 to 2019 and were conducted in six countries including China (n = 5) [21, 22, 25, 27, 32], Korea (n = 4) [20, 26, 29, 31], Japan (n = 3) [11, 12, 30], Austria (n = 1) [24], Poland (n = 1) [28], and Turkey (n = 1) [23]. The sample sizes ranged from 113 to 1551, with a median value of 186.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The major characteristics of the 15 eligible studies are presented in Table 1. These studies were published from 2015 to 2019 and were conducted in six countries including China (n = 5) [21, 22, 25, 27, 32], Korea (n = 4) [20, 26, 29, 31], Japan (n = 3) [11, 12, 30], Austria (n = 1) [24], Poland (n = 1) [28], and Turkey (n = 1) [23]. The sample sizes ranged from 113 to 1551, with a median value of 186.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [12, 20, 2225, 29, 30] investigated the prognostic value of PLR in UTUC while seven studies focused on BC [11, 21, 2628, 31, 32]. Regarding the prognostic role of PLR in UC, nine studies reported OS [11, 12, 21, 2426, 28, 31, 32], seven studies reported PFS [2225, 27, 29, 30], six studies reported DFS [20, 22, 23, 27, 29, 30], and five studies provided data on CSS [11, 20, 26, 28, 31]. All studies had NOS scores ≥ 6.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations